2014
DOI: 10.1186/s13568-014-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse allosteric and catalytic functions of tetrameric d-lactate dehydrogenases from three Gram-negative bacteria

Abstract: NAD-dependent D-lactate dehydrogenases (D-LDHs) reduce pyruvate into D-lactate with oxidation of NADH into NAD + . Although non-allosteric D-LDHs from Lactobacilli have been extensively studied, the catalytic properties of allosteric D-LDHs from Gram-negative bacteria except for Escherichia coli remain unknown. We characterized the catalytic properties of D-LDHs from three Gram-negative bacteria, Fusobacterium nucleatum (FNLDH), Pseudomonas aeruginosa (PALDH), and E. coli (ECLDH) to gain an insight into allost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…In general, divalent metal ions have diverse effects on the catalytic activity of LDHs from different bacterial sources. In a study by Furukawa, Miyanaga, Togawa, Nakajima, and Taguchi (), Ca 2+ was shown to have a significant activation effect on Pseudomonas aeruginosa D‐LDH, whereas having no influence on Fusobacterium nucleatum D‐LDH and E. coli D‐LDH (). Furthermore, Mg 2+ activated F .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, divalent metal ions have diverse effects on the catalytic activity of LDHs from different bacterial sources. In a study by Furukawa, Miyanaga, Togawa, Nakajima, and Taguchi (), Ca 2+ was shown to have a significant activation effect on Pseudomonas aeruginosa D‐LDH, whereas having no influence on Fusobacterium nucleatum D‐LDH and E. coli D‐LDH (). Furthermore, Mg 2+ activated F .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Mg 2+ activated F . nucleatum D‐LDH and P. aeruginosa D‐LDH, but was unable to activate E. coli D‐LDH (Furukawa et al., ). Jiang et al., reported that Ca 2+ activated B .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations